Apical hypertrophic cardiomyopathy: diagnosis, medical and surgical treatment - Paluszkiewicz, Jerzy; Krasinska, Beata; Milting, Hendrik; Gummert, Jan; Pyda, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
Apical hypertrophic cardiomyopathy (AHCM) is a rare form of hypertrophic cardiomyopathy, occasionally resulting in severe complications. The paper covers the etiology and pathogenesis of AHCM, different imaging methods and characteristic appearance of the disease in each of them. Echocardiography and cardiovascular magnetic resonance imaging (CMR) are known to be the most valuable imaging methods. Moreover, this review presents medical and surgical treatment, as well as the clinical course and prognosis. Despite possible morbid events the overall cardiovascular mortality rate of AHCM patients is low, and the prognosis is relatively optimistic.